Challenges in the Gynecologic Care of Premenopausal Women With Breast Cancer - Bakkum-Gamez, Jamie N. (Mayo Foundation for Medical Education and Research, 2011)
Premenopausal women with a new diagnosis of breast cancer are faced with many challenges. Providing health care for issues such as gynecologic comorbidities, reproductive health concerns, and vasomotor symptom control can be complicated because of the risks of hormone treatments and the adverse effects of adjuvant therapies. It is paramount that health care professionals understand and be knowledgeable about hormonal and nonhormonal treatments and their pharmacological parameters so they can offer appropriate care to women who have breast cancer, with the goal of improving quality of life. Articles for this review were identified by searching the PubMed database with no date limitations. The following search terms were used: abnormal uterine bleeding, physiologic sex steroids, endometrial ablation, hysteroscopic sterilization, fertility preservation in endometrial cancer, tranexamic acid and breast cancer, menorrhagia treatment and breast cancer, abnormal uterine bleeding and premenopausal breast cancer, levonorgestrel IUD and breast cancer, tamoxifen and gynecologic abnormalities, tamoxifen metabolism, hormones and breast cancer risk, contraception and breast cancer, pregnancy and breast cancer, and breast cancer and infertility treatment.